Cosmopolitan Norms and European Values : Ethical Perspectives on Europe's Refugee Policy. - Göbel, Marie. (Routledge Studies in Contemporary Philosophy Series, 2023)
This volume offers a philosophical analysis of the normative challenges facing European refugee policy. By considering the refugee policy through the lens of European values, cosmopolitan norms, and universal human rights, the chapters expose the limitations of existing regulations and propose how to improve them.